Baseline perihematomal edema, C-reactive protein, and 30-day mortality are not associated in intracerebral hemorrhage - Sobowale, Oluwaseun A.; Hostettler, Isabel C.; Wu, Teddy Y.; Heal, Calvin; Wilson, Duncan; Shah, Darshan G.; Strbian, Daniel; Putaala, Jukka; Tatlisumak, Turgut; Vail, Andy; Sharma, Gagan; Davis, Stephen M.; et al. (Frontiers in Neurology, 2024)
Background The relationship between baseline perihematomal edema (PHE) and inflammation, and their impact on survival after intracerebral hemorrhage (ICH) are not well understood. Objective Assess the association between baseline PHE, baseline C-reactive protein (CRP), and early death after ICH. Methods Analysis of pooled data from multicenter ICH registries. We included patients presenting within 24 h of symptom onset, using multifactorial linear regression model to assess the association between CRP and edema extension distance (EED), and a multifactorial Cox regression model to assess the association between CRP, PHE volume and 30-day mortality. Results We included 1,034 patients. Median age was 69 (interquartile range [IQR] 59–79), median baseline ICH volume 11.5 (IQR 4.3–28.9) mL, and median baseline CRP 2.5 (IQR 1.5–7.0) mg/L. In the multifactorial analysis [adjusting for cohort, age, sex, log-ICH volume, ICH location, intraventricular hemorrhage (IVH), statin use, glucose, and systolic blood pressure], baseline log-CRP was not associated with baseline EED: for a 50% increase in CRP the difference in expected mean EED was 0.004 cm (95%CI 0.000–0.008, p = 0.055). In a further multifactorial analysis, after adjusting for key predictors of mortality, neither a 50% increase in PHE volume nor CRP were associated with higher 30-day mortality (HR 0.97; 95%CI 0.90–1.05, p = 0.51 and HR 0.98; 95%CI 0.93–1.03, p = 0.41, respectively). Conclusion Higher baseline CRP is not associated with higher baseline edema, which is also not associated with mortality. Edema at baseline might be driven by different pathophysiological processes with different effects on outcome.